2014
DOI: 10.1099/jmm.0.060632-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with Chlamydia psittaci infection in psittacine birds

Abstract: Chlamydia psittaci is the aetiological agent of chlamydiosis in birds, especially Psittaciformes. The objective of the present study was to detect C. psittaci by means of semi-nested PCR among psittacine birds sold at pet markets and kept as pet birds in Salvador, Bahia, Brazil. Questionnaires were used to identify risk factors involved in the epidemiology of the disease. In addition, the management of birds and cages was observed at each location studied. The frequency of C. psittaci infection was 10.6 % (33/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
2
11
0
1
Order By: Relevance
“…For example, the predominance of cloacal excretion, as observed in the present study, indicates that animals are chronically infected, whereas greater levels of bacteria in the oropharynx suggest earlier stages of infection. Similarly, in a study with 311 psittacids from commercial establishments and owners in Salvador (Bahia State, Brazil), the incidence of Chlamydophila infection was 10.6% (33/311), with 9.3% (29/311) confirmed from cloacal samples and only 1.3% (4/308) confirmed from oropharynx samples (SANTOS et al, 2014). This indicates a pattern of chronic and persistent contamination in breeding sites, as observed in the present study.…”
Section: Resultssupporting
confidence: 85%
“…For example, the predominance of cloacal excretion, as observed in the present study, indicates that animals are chronically infected, whereas greater levels of bacteria in the oropharynx suggest earlier stages of infection. Similarly, in a study with 311 psittacids from commercial establishments and owners in Salvador (Bahia State, Brazil), the incidence of Chlamydophila infection was 10.6% (33/311), with 9.3% (29/311) confirmed from cloacal samples and only 1.3% (4/308) confirmed from oropharynx samples (SANTOS et al, 2014). This indicates a pattern of chronic and persistent contamination in breeding sites, as observed in the present study.…”
Section: Resultssupporting
confidence: 85%
“…The higher frequency of C. psittaci in cloacal swabs compared to choanal ones suggests longer time post exposure to the bacteria, once initial infections tend to stay primarily in the respiratory tract, being subsequently eliminated in feces (Andersen, 1996). These results corroborate to previous report (Santos et al, 2014;Raso et al, 2006) where C. psittaci semi-nested PCR detection in psittacine birds was more frequently in cloaca samples than oropharynx and tracheal ones. However, in another study (Andersen, 1996), it was found greater isolation rate of C. psittaci in cockatiels (Nymphicus hollandicus) from pharyngeal swabs (80.4%), while fecal and cloacal resulted in positivity of 45.1% and 37.3%, respectively.…”
Section: Frequency Of C Psittaci In the Macaws Evaluatedsupporting
confidence: 90%
“…Also, the fact that fewer infected birds were raised in cages (36%) than in aviaries (82%) suggests that the environmental, management, and hygienic conditions of the birds kept in households and cages reduces the chance of C. psittaci infection (Santos et al . ). The high prevalence of C. psittaci infections in psittacine birds raised in pet markets and aviaries may be explained by the mixed feeding, stress factors, the dirty and stuffy environment at pet markets, in addition to birds being traded at a young age (Zhang et al .…”
Section: Discussionmentioning
confidence: 97%
“…Chlamydia psittaci infections in psittacine birds have been reported previously in Brazil (Santos et al . ), China (Zhang et al . ), Japan (Saito et al .…”
Section: Introductionmentioning
confidence: 99%